Effect of Think Pair Share on Fourth Graders Communication Skills at SDN 1 Panongan - Setiawan, Adang; Rahmah, Vina Fitria; Vebrianty, Shahira Wanda; Simbolon, Melati; Hayati, Auliya Aenul (Juwara: Jurnal Wawasan dan Aksara, 2025)
The low level of students’ communication skills in Civic Education remains a major concern, largely due to the dominance of conventional teaching methods that limit active student participation. This study aimed to examine the effectiveness of the Think Pair Share (TPS) learning model in improving the communication skills of fourth-grade students at SDN 1 Panongan. A quantitative approach with a quasi-experimental nonequivalent control group design was employed. The sample consisted of two fourth-grade classes: class IVA as the experimental group receiving TPS instruction and class IVB as the control group using conventional teaching methods. Data were collected through communication skills tests administered before and after the intervention. The results indicated that the experimental group achieved a higher mean posttest score (80.32) than the control group (67.14). The t-test analysis revealed a significant difference between the two groups (t = 18.020, p < 0.05). In addition, the N-Gain analysis showed a moderate improvement in the experimental group (0.53) and a low improvement in the control group (0.25). These findings demonstrate that the Think Pair Share model is an effective instructional approach for enhancing students’ communication skills in elementary Civic Education.